STATUS AND EFFECTS OF USING MULTI-MICRONUTRIENT SUPPLEMENTATION DURING PREGNANCY IN LOW-MIDDLE INCOME COUNTRIES AND DEVELOPING COUNTRIES: ARTICLE REVIEW - Aliya Rosyidah Fitrianti; Neng Sani Nurbaniyah; Zhafira Al-Aliya (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Multiple-micronutrient (MMS) supplements are recommended for pregnant women to support both fetal growth and maternal health, addressing increased nutritional needs during pregnancy. Essential nutrients include folic acid, iron, calcium, vitamin D, and other vitamins and minerals. MMS supplements, which combine these nutrients, are more commonly used in developed countries compared to low- and middle-income countries (LMICs), where many women have poor diets lacking essential nutrients. To study the usage of MMS in different regions, researchers used keywords like “Pregnant Woman” AND “Multi-micronutrient supplementation (MMS)” AND “Low-middle Income Country” AND “Developed Country” and Boolean operators to find relevant articles. Screening of these articles led to a Systematic Literature Review. Research indicates that over 80% of women in three LMICs (India, DRC, Guatemala) have inadequate nutritional intake, especially in the first trimester, justifying the need for MMS. In developed countries, many women also fail to meet recommended intakes of folic acid, iron, and vitamin D despite an overall increase in energy intake and weight gain during pregnancy. This inadequate nutritional intake can lead to complications and congenital malformations. Both in LMICs and developed countries, studies show that the intake of MMS supplements among pregnant women does not meet recommendations. Therefore, there is a need to optimize policies promoting MMS supplementation to prevent nutritional deficiencies during pregnancy.